Back to Roots: The Role of Ectomycorrhizal Fungi in Boreal and Temperate Forest Restoration - Policelli, Nahuel; Horton, Thomas R.; Hudon, Aimée T.; Patterson, Taylor R.; Bhatnagar, Jennifer M. (Frontiers in Forests and Global Change, 2020)
Temperate and boreal forests are increasingly suffering from anthropic degradation. Ectomycorrhizal fungi (EMF) are symbionts with most temperate and boreal forest trees, providing their hosts with soil nutrients and water in exchange for plant carbon. This group of fungi is involved in woody plants’ survival and growth and helps plants tolerate harsh environmental conditions. Here, we describe the current understanding of how EMF can benefit temperate and boreal forest restoration projects. We review current evidence on promising restoration plans that actively use EMF in sites contaminated with heavy metals, affected by soil erosion, and degraded due to clearcut logging and wildfire. We discuss the potential role of this group of fungi for restoring sites invaded by non-native plant species. Additionally, we explore limitations, knowledge gaps, and possible undesired outcomes of the use of EMF in forest restoration, and we suggest how to further incorporate this fungal group into forest management. We conclude that considering EMF – host interactions could improve the chances of success of future restoration programs in boreal and temperate forests.